2011
DOI: 10.1063/1.3634150
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on polarized surface enhanced resonance Raman scattering of rhodamine 6G adsorbed on porous Al2O3 substrates

Abstract: The polarization properties of surface enhanced resonance Raman scattering (SE(R)RS) of rhodamine 6G molecules, adsorbed to a hexagonally ordered gold nanostructure, are studied with the purpose to discriminate between adsorption sites with different plasmonic properties. The nanostructure is based on a self-organizing hexagonally ordered porous Al(2)O(3) substrate sputter-coated with gold. Each hexagonal subunit has D(6h) symmetry, where the symmetry center may act as an isotropic site, whereas the six narrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…For comparison, in Figs S3 and S4, we also displayed the spectra for the Ag 3 complexes. As discussed previously, these types of complexes are able to form well‐organized interfacial intermolecular systems. Hence, we have determined the depolarized light scattering properties for specific vibrational modes, directly involved in the intermolecular interactions.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…For comparison, in Figs S3 and S4, we also displayed the spectra for the Ag 3 complexes. As discussed previously, these types of complexes are able to form well‐organized interfacial intermolecular systems. Hence, we have determined the depolarized light scattering properties for specific vibrational modes, directly involved in the intermolecular interactions.…”
Section: Resultssupporting
confidence: 65%
“…Because these types of complex are able to form well‐organized interfacial intermolecular systems, Raman light‐scattering properties were also calculated for important Raman‐active bands of the complexes. The differential cross sections of depolarized Raman scattering observed at right angles to the incident beam are determined by the activities, whereas the depolarization ratios for both natural and plane‐polarized light are, respectively, given by ρn=6Δα'245αtrue¯'2+7Δα'2 ρp=3Δα'245αtrue¯'2+4Δα'2 where falseα¯' and Δα ' are the derivatives of the average and anisotropic dipole polarizabilities.…”
Section: Methods and Calculationsmentioning
confidence: 99%
“…Under ambient conditions, Ag thin film was oxidized, ended up with a shiny white appearance. In this case, weak C-C stretching modes were also observed from R6G at 1140, 1450 and at 1680 cm −1 33 40 , which proves the improved enhancement of Ag/Ag 2 O thin films with respect to Ag thin films. As a function of film thickness, we found that the highest enhancement was observed from 10 nm Ag/Ag 2 O films (the enhancement observed from 100 nm films were also similar to that of 50 nm films, therefore it is not shown here for brevity).…”
Section: Resultsmentioning
confidence: 54%
“…Instead of using polymer or silica spheres as the template, porous Al 2 O 3 produced by different anodizing techniques can be applied. [332][333][334] These nanoporous templates are versatile platforms for sensing, storage and separation applications and are created by a two-step anodization of a thin aluminum film on the surface of silicon substrates (anodic aluminum oxide, AAO). The porous size and depths are controlled by the anodic oxidation.…”
Section: Template Based Methodsmentioning
confidence: 99%